Evaluate abs(2 x - 7) - 3 where x = 2:abs(2 x - 7) - 3 = abs(2 2 - 7) - 3
2×2 = 4:abs(4 - 7) - 3
4 - 7 = -3:abs(-3) - 3
Since -3<=0, then abs(-3) = 3:3 - 3
3 - 3 = 0:Answer: 0
32,870 is the answer. Hope this helps!
Answer: #20, x = 3
#21, x = 1/2
Step-by-step explanation:
#20) x + 4 + x + 2+ x + 5 = x + 3 +x+3+x+1+x+1
3x + 11 = 4x + 8
<u>-3x -3x</u>
11= x + 8
<u> - 8 - 8</u>
3 = x
#21) 12x(5) = 6x + 9 + x + 10 + x + 7
60x =8x + 26
<u> -8x -8x</u>
52x = 26
divide both sides by 52
x = 1/2
Answer:
I dont understand comment on this and i can help you out
Step-by-step explanation:
:)